Venerating a Pagan Prophecy: The ara coeli Legend between Humanist Erudition, Reformation Theology, and Popular Piety - Schulze-Feldmann, Finn (Renaissance and Reformation / Renaissance et Réforme, 2022)
This article examines the ara coeli legend, a tale in which the Tiburtine Sibyl showed Emperor Augustus a vision of a virgin holding a child proclaiming the child’s greatness. Based on both texts and art works, mainly from the Holy Roman Empire, it argues that the legend owed its widespread popularity to the way in which it was grafted onto the fifteenth-century Marian cult. While flourishing in coexistence with the humanist reconsideration of the Sibylline heritage, this incorporation into popular belief ultimately led to the legend’s decline during the Reformation, as reformers and later Catholic theologians revised Mary’s role in the unfolding of Christian salvation. In the face of Protestant and post-Tridentine theology, the ara coeli legend thus subsided into religious irrelevance, giving way to political, mythological, and gendered interests in the Sibyls.